2009
DOI: 10.1021/jo901843w
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Lactams Using Domino Reactions: Combination of Schmidt Reaction with Sakurai and Aldol Reactions

Abstract: A series of domino reactions in which the intramolecular Schmidt reaction is combined with either a Sakurai reaction, an aldol reaction, or both is reported. The Sakurai reaction of an allylsilane with an azido-containing enone under Lewis acidic conditions followed by protonation of the resulting titanium enolate species allowed for a subsequent intramolecular Schmidt reaction. Alternatively, the intermediate titanium enolate could undergo an aldol reaction, followed by the intramolecular Schmidt reaction to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Work in this laboratory has utilized nucleophilic addition to 3-azidoalkanals as one component of intramolecular azido-Schmidt domino reactions (Scheme ). For example, we recently reported a domino Sakurai/aldol/Schmidt reaction that involved an aldol addition of an in situ generated titanium enolate species to 3-azidononanal. Notably, this reaction resulted in the exclusive formation of a 1,3- syn aldol intermediates ( 1a and 1b ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Work in this laboratory has utilized nucleophilic addition to 3-azidoalkanals as one component of intramolecular azido-Schmidt domino reactions (Scheme ). For example, we recently reported a domino Sakurai/aldol/Schmidt reaction that involved an aldol addition of an in situ generated titanium enolate species to 3-azidononanal. Notably, this reaction resulted in the exclusive formation of a 1,3- syn aldol intermediates ( 1a and 1b ).…”
mentioning
confidence: 99%
“…The azido group is electron-withdrawing and has the ability to chelate with metal species. ,, Therefore, one would expect that it should behave similarly to an alkoxy group at the 3-position of an aldehyde, which can participate in chelation via Reetz’s chelation model or act as an electron-withdrawing group via Evans’s non-chelation model, both of which should lead to a 1,3- anti product based on the preceding analysis. However, since the above-noted precedents (Scheme ) suggested 1,3- syn selective nucleophilic addition to 3-azidoalkanals under chelation conditions, we decided to further investigate the stereoselectivity of these processes.…”
mentioning
confidence: 99%
“…Conversion of the acetal to a reactive oxonium ion and attachment of 4 yields a cyclopropyl cation that undergoes ring expansion to afford a mixture of three spirocyclobutanone diastereomers, of which 5a was predominant. Not only would this approach afford a concise entry into the appropriately functionalized ring system, but the use of Lewis acid in the key step suggested that incorporation of an azide into the starting acetal (or its equivalent) might lead directly into a subsequent Schmidt-styled ring expansion of the cyclobutanone adduct to achieve the 5,6,6-tricyclic lactam. , …”
mentioning
confidence: 99%
“…Since compounds 3 a,b represent the first and only examples of 4,5-dihydro-1,2,3,4-oxatriazoles, the results reported in 2002 were cited and reviewed repeatedly. [2] The well-known [3] transformation of 4 a and 4 b into 5 a,b and 5 c, respectively, seems to be similar to the formation of 3 a,b from 2 a,b. However, the question arises whether the carbonyl group of an aldehyde and an azido unit are thermodynamically more favorable than a nonaromatic 4,5-dihydro-1,2,3,4-oxatriazole that includes a weak O À N single bond.…”
Section: Introductionmentioning
confidence: 84%